2019
DOI: 10.1002/anie.201910594
|View full text |Cite
|
Sign up to set email alerts
|

Difluoro(aryl)(perfluoroalkyl)‐λ4‐sulfanes and Selanes: Missing Links of Trichloroisocyanuric Acid/Potassium Fluoride Chemistry

Abstract: The TCICA/KF approach to oxidative fluorination of heteroatoms has emerged as a surprisingly simple, safe, and versatile surrogate to classically challenging fluorination reactions. Although polyfluorination (or chlorofluorination) of diaryl disulfides, diaryl diselenides, diaryl ditellurides, aryl iodides, and aryl(perfluoroalkyl)tellanes has been described, the application of this TCICA/KF methodology to aryl(perfluoroalkyl)sulfanes and selanes remains an area of unexplored chemical space. Accordingly, to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…SF 3 group containing compounds can be oxidized by various methods to access SF 5 or SF 4 Cl moieties [16] . For instance, it has been shown that trichloroisocyanuric acid (TClCA) can be used for an oxidation of disulfides to access after subsequent fluorination SF 5 groups [16v,w,17] . In contrast, treatment of 6 with 10 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…SF 3 group containing compounds can be oxidized by various methods to access SF 5 or SF 4 Cl moieties [16] . For instance, it has been shown that trichloroisocyanuric acid (TClCA) can be used for an oxidation of disulfides to access after subsequent fluorination SF 5 groups [16v,w,17] . In contrast, treatment of 6 with 10 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…With the Ar‐S‐Phth precursors ( 3 ) in hand, we set out to explore the second step of the synthetic route. Inspired by the remarkable findings recently reported by Pitts, Santschi and Togni en route to fluorinated aryl‐S(VI), [7b] ‐Te IV [25] and ‐Se IV [26] compounds from ArCh‐ChAr, we attempted the oxyfluorination of Ph‐S‐Phth with a mixture of trichloroisocyanuric acid (TCICA) and potassium fluoride (KF), in the presence of additives. During our initial oxidation experiments, we were pleased to observe the formation of the rare Ph‐SOF 3 ( 4 a ), [10] accompanied by large amounts of PhSO 2 F ( 5 a ) and PhSF 4 Cl ( 6 a ).…”
Section: Figurementioning
confidence: 99%
“…Over the last two years, the Togni group has reported applications of an exceptionally mild approach to oxidative fluorination of heteroatoms in organic frameworks using trichloroisocyanuric acid (TCICA) and potassium fluoride. This ‘TCICA/KF’ approach has been leveraged in the fluorination of aryl‐ and perfluoroalkyl‐substituted organochalcogens [1–3] and aryl iodides [4] ( Figure 1), and it has effectively established a much‐needed detour around hazardous reagents such as XeF 2 , HF, SF 4 , Cl 2 and F 2 . While initial investigations were primarily focused on group 16 and 17 elements, we recently realized an opportunity to extend this approach to group 15 elements, thereby enabling the synthesis of fluorinated organophosphorus(V) compounds.…”
Section: Introductionmentioning
confidence: 99%